Infliximab, azathioprine or combination therapy in the treatment of active Crohn''s disease. (December 2010) - Cottone, Mario; Papi, Claudio; Orlando, Ambrogio
Evaluation of: Colombel JF, Sandborn WJ, Reinisch W et al. ; for the SONIC Study Group. Infliximab, azathioprine, or combination therapy for Crohn''s disease. N. Engl. J. Med. 362, 1383––1395 (2010). The treatment of moderate-to-severe steroid-dependent Crohn''s disease has been a challenging issue for the gastroenterologist. Until to 10 years ago, immunosuppressors, mainly azathioprine or 6-mercaptopurine, were the best possible treatments available, and remission rates ranged from 30 to 60% according to the results of open studies and controlled trials. Recently, infliximab has been shown to be effective in steroid-dependent patients and, combined with azathioprine, it has been shown to increase 1-year remission rates. A recent large randomized controlled trial comparing infliximab, azathioprine and infliximab plus azathioprine demonstrated that the combination of infliximab plus azathioprine is the most suitable treatment for obtaining steroid-free remission after 26 weeks: steriod-free remission was obtained in 56% of the patients in the infliximab plus azathioprine group versus 44% of patients receiving infliximab alone and 30% of patients receiving azathioprine alone. No relevant differences were observed in the rate of side effects in the three groups of treatments. In this article, the results of this trial are discussed.